Who is willing to pay to see the Big 7? - Saayman, Melville; Saayman, Andrea (IP Publishing, 2014)
This article investigates the non-consumptive, or appreciative value of the 'Big 7' and identifies the variables that influence willingness to pay (WTP). Addo Elephant National Park in the Eastern Cape Province, South Africa, is one of few places in the world where tourists can view all seven species: lion, buffalo, rhinoceros, leopard, elephant, southern right whale and great white shark. Two surveys were conducted, using the same questionnaire, one during summer and one during winter. A total of 232 completed questionnaires were used in the Heckman model selection procedure. The findings revealed that, although a variety of socio-demographic, behavioural and motivational factors influence the amount respondents are willing to pay, there is a clear distinction between the determinants for land species compared to marine species. This poses challenges for the marketing of and establishment of the Big 7 as a brand.